Efeitos do esteróide anabolizante associado à fisioterapia no desmame da ventilação mecânica em crianças - Franz, Flávia (2011)
AIM: To verify the effects of an anabolic steroid (nandrolone decanoate) associated to physical therapy in prolonged mechanical ventilation weaning in children.METHODS: This is a historical observational cohort study. Twenty nine children with difficult weaning or that showed high numbers of extubation failure needing repeated ventilatory support were included in the study. As they showed two or more dysfunctions they were classified according to the score: systemic (characterized by malnutrition), respiratory, cardiac, neurologic and musculoskeletal dysfunctions. All children were submitted to respiratory and motor therapy 2 to 3 times a day. Parameters as time and ventilation weaning, extubation failures, weight gain, length of hospitalization and survival were evaluated.RESULTS: The length of mechanical ventilation before and after the use of anabolic steroid was similar (p=0.758). The number of failures before the use of AS was significant higher when compared to after AS (P<0.001). After the use of the drug 20 children (69%) did not show any failure at the moment of mechanical ventilation removal. Twenty six children (89.7%) showed success in weaning and three did not respond to the treatment. After the first dose of AS until mechanical ventilation removal and hospital release the patients showed significant weight gain (p<0.05). Tracheostomized children showed higher length of mechanical ventilation (p<0.001) however, this result did not interfere in mortality rate. After one year of treatment, 73.1% survived. After twenty months the survival probability was of 50.3% and after this period no modifications were observed. All death occurred in this 20 months interval.CONCLUSION: the use of AS associated to a MV weaning protocol can facilitate MV weaning and improve strength and resistance performance of children who stayed for long periods in MV. It promotes weight gain and reduces the number of MV extubation failure and it is efficient in children showing malnutrition with multiple dysfunctions and critically sick. It is not associated to the increase of mortality.